This is why we lied - Slaughter, Karin, 1971- (Slaughter, Karin, 1971- Will Trent series, 2024)
"For GBI investigator Will Trent and medical examiner Sara Linton, McAlpine Lodge seems like the ideal getaway to celebrate their honeymoon. Set on a gorgeous, off-the-grid mountaintop property, it's the perfect place to unplug and reconnect. Until a bone-chilling scream cuts through the night. Mercy McAlpine, the manager of the Lodge, is dead. With a vicious storm raging and the one access road to the property washed out, the murderer must be someone on the mountain. But as Will and Sara investigate the McAlpine family and the other guests, they realize that everyone here is lying....Lying about their past. Lying to their family. Lying to themselves. It soon becomes clear that normal rules don't apply at McAlpine Lodge, and Will and Sara are going to have to watch their step at every turn. Trapped on the resort, they must untangle a decades-old web of secrets to discover what happened to Mercy. And with the killer poised to strike again, the trip of a lifetime becomes a race against the clock..."--